MEMBANGUN USAHA KREATIF, INOVATIF DAN BERMANFAAT MELALUI PENERAPAN KEWIRAUSAHAAN SOSIAL PADA UMKM SATYAGRAHA DI KOTA DENPASAR - Anggraeni Nisa Rachmawati; Ni Luh Ketut Ayu Sudha Sucandrawati; Ni Putu Andini Desiyanti Laksmi (KOLONI, 2022)
Entrepreneurship can be in the form of an imaginative and inventive capacity, keen to see gaps and continuously open to any input and positive changes that can bring trade to continue to grow and have self-respect. The purpose of this study was to determine the effect of creativity, beneficial innovation on the entrepreneurship of MSME Sukla Satyagraha. One of the pioneers of developing MSME in Bali is the Satyagraha Movement. The Satyagraha movement is a culinary business movement as well as traders with micro and medium enterprises which is a form of economic empowerment of Balinese manners that adheres to Hindu ethics as well as synergizes between ancestral concepts and modern generation concepts that have undergone various forms of change. Being an innovator has advantages, that's what Panada Store respondents, Laklak Bu Nyoman and Jaje Bali Jaen, did. Although there are now many who sell pastels, Balinese laklak and traditional Balinese snacks with a similar concept, the Panada Store brand has already been known as a seller of pastels that have wrappers like bread. Mrs. Nyoman's Laklak is known as laklak by using firewood stoves and Mrs. Komang's Jaje Bali Jaen which has various variants compared to other traditional snack entrepreneurs. In addition, in this case, businesses that sell products that follow this similar concept cannot be considered as innovations, because they are considered to have imitated or modified existing products with the same market. Business owners also set creative solutions to overcome the problem of changing culinary trends. Keywords: Creativity, Innovation, Social Entrepreneurship, MSME, Gerakan Sukla Satyagraha